Tolerance mechanisms in mercury-exposed Chromolaena odorata (l.f.) R.M. King et H. Robinson, a potential phytoremediator - H J P Alcantara; G C Rivero; J M Puzon (Brawijaya University, 2013)
Chromolaena odorata (L.f.) R.M. King et H. Robinson plants were grown in Hoagland’s solutions with 0.00 ppm and 1.00 ppm Hg(NO3)2. The calcium, magnesium, iron, and sulfur levels in the leaves were found to be not significantly affected by presence of the uptaken Hg2+. The chlorophyll a, chlorophyll b, and total chlorophyll contents of its leaves also remained within normal levels, which may indicate that the photosynthetic machinery of the Hg-exposed C. odorata was unaffected by the presence of Hg2+. The results of the ICP-AES analyses of the Hg2+ contents established the presence of Hg2+ in all the subcellular components obtained from the leaves of the Hg-treated C. odorata plants, and that the ultimate localization of Hg2+ is in the vacuoles. The findings revealed no significant differences in the degree of oxidative injury between the cells from the control and Hg-treated plants, as evidenced by the low lipid peroxidation levels obtained with the TBARS assay. The SH-containing biomolecules that were initially detected through DTNB assay manifested a predominant peak in the RP-HPLC chromatographs of both the control and Hg-treated plants, with their retention times falling within the ranges of GSH, MT, and cysteine standards. However, the concentrations of the GSH- and/or MT-like, Cys-containing biomolecules detected in the leaves of Hg-treated C. odorata plants were ten times higher than those of the control.The findings of this study suggest that the enhanced antioxidative capacity, the production of Hg-binding biomolecules, and the localization of Hg2+ ions ultimately in the vacuoles of the leaves are the mechanisms which bring about Hg2+ tolerance and homeostasis in C. odorata plant. These results indicate that C. odorata is a potentially effective phytoremediator for Hg2+.